Participación de la mujer en el desarrollo de la actividad pesquera artesanal de Puerto Bolívar, año 2021 - Zambrano Paladines, Bryan Manuel; Bueno Macias, Juleysi Del Cisne (Machala: Universidad Técnica de Machala, 2022)
This research, in the context of the degree work, addresses the issue of women's participation in the development of artisanal fishing activity in Puerto Bolivar, year 2021. The social and economic productive context of this activity reveals the low level of participation of women, who are relegated to certain specific functions in areas of the productive chain of processing and commercialization of artisanal fishing products, as a direct consequence of the weak organization of this social group, in order to enforce their rights to labor equality and equal remuneration with men. This is compounded by the prevalence of macho patterns in the managers or leaders of the trade and associations eminently dominated by men who do not see this gender as equal. Under this taxing and discriminatory scenario of women's labor capacities in the artisanal fishing activity in the urban parish of Puerto Bolivar, the general objective of the study is to determine the incidence of women's participation in the development of artisanal fishing activity in this maritime sector of the Machala Canton. In the same way, the socio-economic level of women who participate in the artisanal fishing activity is identified, as well as the determination of their role in this activity and its influence in terms of their social inclusion in gender equity from their dynamics established in the organization of women participants in artisanal fishing. The methodology of the study is epistemologically focused on empirical-inductive research, analytical-synthetic method, with a mixed methodological character in view of the use of combined research tools such as the survey, the documentary review that theoretically supports the research problem, the interview and its orientation to women who participate in artisanal fishing activities, distributed in 122 surveys to legally constituted organizations or associations, 88 to women belonging to de facto fishing organizations and 63 who work in an inductive manner, the interview and its orientation to the women who participate in the artisanal fishing activity, distributed in 122 surveys to legally constituted organizations or associations, 88 to women belonging to de facto fishing organizations and 63 who work independently or who do not belong to any de jure or de facto guild in the artisanal fishing of the Parish, giving a total population of 273 women. In addition, interviews were conducted with leaders and members of the Union of Artisanal Fishing Production Organizations of El Oro UOPPAO, and participant observation through community workshops, which facilitated the interpretative analysis for the triangulation of results in accordance with the research objectives regarding women's participation in the development of artisanal fishing activities in Puerto Bolivar.
La presente investigación, en el contexto del trabajo de titulación aborda la temática sobre la participación de la mujer en el desarrollo de la actividad pesquera artesanal de Puerto Bolívar, año 2021. En su contexto social y económico productivo de esta actividad se pone en evidencia el bajo nivel de participación de la mujer quien es relegada a ciertas funciones específicas en áreas de la cadena productiva de faenamiento y comercialización de los productos de la pesca artesanal, como consecuencia directa de la débil organización de este grupo social, para hacer respetar sus derechos a la igualdad laboral y a una remuneración paritaria a la de los hombres. A esto se suma la prevalencia de patrones machistas en los directivos o dirigentes del comercio y asociaciones eminentemente dominadas por hombres que no consideran la igualdad de este género. Bajo este escenario impositivo y discriminatorio de las capacidades laborales de la mujer en la actividad pesquera de tipo artesanal, en la Parroquia urbana de Puerto Bolívar, surge como objetivo general la determinación de la incidencia de la participación femenina en el desarrollo de la actividad pesquera artesanal de este sector marítimo del Cantón Machala. De la misma manera se identifica el nivel socio-económico de la mujer que participa de la actividad pesquera artesanal, como también la incidencia de su rol y su influencia en términos de inclusión social y equidad de género desde las dinámicas establecidas en la organización de las mujeres participantes de la pesca artesanal. La metodología de estudio está enfocada epistemológicamente a la investigación de tipo empírico-inductiva, método analítico – sintético, con carácter metodológico mixto en vista de la utilización de herramientas de investigación combinados tales como la encuesta, la revisión documental que fundamenta teóricamente el problema de investigación, la entrevista y su orientación a las mujeres que participan de la actividad pesquera artesanal, distribuidas en 122 encuestas a organizaciones y asociaciones legalmente constituidas, 88 a mujeres pertenecientes a organizaciones pesqueras de hecho y 63 que laboran de manera independiente o que no pertenecen a ningún gremio de derecho en la pesca artesanal de la Parroquia, dando una población total de 273 mujeres. Además, se realizaron entrevistas orientadas a líderes y dirigentes agremiados en la Unión de Organizaciones de Producción Pesquera Artesanal de El Oro UOPPAO, y la observación, que facilitaron el análisis interpretativo para la triangulación de resultados acordes a los objetivos de investigación planteados en la participación de la mujer en el desarrollo de la actividad pesquera artesanal de Puerto Bolívar.
Keywords: PARTICIPACION DE LA MUJER; DESARROLLO PESQUERO ARTESANAL; INCLUSION SOCIAL Y LABORAL; LIDERAZGO DEL SECTOR